Leadership Experiences of Managing Technological Change in Teaching, Assessment, and Administrative Systems in Pakistan - Zafar, Dr. Nishat; Andleeb, Dr. Nazish; Khurram, Dr Azmat Farooq Ahmad (ACADEMIA International Journal for Social Sciences, 2025)
Academic institutions are experiencing rapid technological transformation to the educational systems teaching, assessment, and administrative systems, that puts new pressures on educational leadership. This paper discusses leadership experiences in managing change in technology in Pakistani schools and colleges, with implications on how institutional leaders perceive, execute, and react to the digital transformation programs. The research problem tackles the fact that little has been known about leadership sense-making and decision-making in the change caused by technology in education. The main purpose of the study was to focus on the experiences, struggles and methods which leaders have implemented in their process of transitioning associated with digital teaching devices, assessment systems and administrative technology. The qualitative research design was applied, and semi-structured interviews with principals, administrators, and academic leaders of both public and private institutions were used. The researchers made the assumption that organizational culture, availability of resources and accountability pressure determine the manner in which leaders respond to changing technology, and provided a set of boundary conditions based on infrastructure, capacity of staff and policy requirements. The results suggest that the technological change is seen within the leaders as a force of modernization as well as a cause of professional tension, increasing workloads, and resistance management. The results are consistent with global research on educational change leadership and provide domestic details of Pakistan. The research proves that adaptive leadership, relational negotiation, and institutional lasting support are the elements that lead to successful management of technological change.